Dynamic Threshold-based Congestion Control in Wireless Multimedia Networks - Abigaba Mirembe, Cuthbert; Nyongarwizi Akol, Roselyn; Butime, Julius (International Journal of Engineering and Technology, 2013)
The last few decades have seen a tremendous growth of wireless networks demands due to the need to meet different multimedia applications available over the network. The demand has resulted into greater competition for the scarce available network resources and has introduced congestion in such networks that adversely affect the quality of service requirements of the applications. Call admission control is a key element if provision of quality of service in wireless networks is to be guaranteed. In this paper, a call admission control policy for wireless communication networks based on the use of dynamic threshold-based channel allocation scheme is proposed. The scheme deals with two traffic classes; voice and data with two different but equal channel thresholds, one for each traffic type assumed. The effect of the control parameters on the quality of service parameters is illustrated and analyzed.